Current results as reference for future improvements in immunosuppression - Opelz, Gerhard; Döhler, Bernd; Wujciak, Thomas (Immunosuppression under trial, 1999)
The immunosuppressive drug regimen most commonly used for kidney transplant recipients during the last 10 years was a combination of cyclosporine with either steroids or azathioprine, or both. More recently, new immunosuppressive drugs, such as tacrolimus, mycophenolate and rapamycin have been introduced and hopes were raised that these new medications would improve the success rate of kidney grafts. Experience with these new drugs is still limited and long-term follow up is currently not available. The present report provides an overview of results obtained with regimens that were considered `standard’ during the last 10 years. They should serve as a reference against which future improvements can be measured.
Gesehen am 19.02.2021